Multi-Robot Systems: Challenges, Trends and Applications - Roldán Gómez, Juan Jesús; Barrientos, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a printed edition of the Special Issue entitled "Multi-Robot Systems: Challenges, Trends, and Applications" that was published in Applied Sciences. This Special Issue collected seventeen high-quality papers that discuss the main challenges of multi-robot systems, present the trends to address these issues, and report various relevant applications. Some of the topics addressed by these papers are robot swarms, mission planning, robot teaming, machine learning, immersive technologies, search and rescue, and social robotics.